Pengaruh Turnover dan Inventory Turnover terhadap Perubahan Laba pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia (Studi Kasus Pada Perusahaan Pertambangan Periode 2012-2016) - Dewi Ningsih; Maftukhin; Indah Dewi Mulyani; Ayusa Nitasari; Amelia Sholeha (Journal of Accounting and Finance (JACFIN), 2019)
This study aims to determine the effect of liquidity ratios and activity ratios on changes in earnings in mining companies listed on the Indonesia Stock Exchange (IDX). Of the two types of rations the researchers conducted tests for (1) find out the Current Ratio on changes in profits of mining companies Stock Exchange (IDX) (2) Knowing the effect of the Quick Ratio on changes in profit of mining companies listed on the Indonesia Stock Exchange (IDX) (3) knowing the effect of Total Asset Turnover on changes in profits of mining companies listed on the Indonesia Stock Exchange (IDX) (4) Knowing the effect of Inventory Turnover on changes profits on mining companies listed on the Indonesia Stock Exchange (IDX) (5) Knowing the effect of the Current Ratio, Quick Ratio, Total Asset Turnover, Inventory Turnover on changes in mining profits listed on the Indonesia Stock Exchange (IDX). The population used in this study is a mining company listed on the Indonesia Stock Exchanges (IDX). While the selection of samples in taken using the purposive sampling method. The number of samples is 14 mining companies listed on the Indonesia Stock Exchange (IDX) in the 2012-2016 period. The data obtained is secondary data with using the classical assumption testing documentation data used in this study is to use the Multicollinearity test, normality test, Autocorrelation test, Heteroscedasticity test and linearity test. Data analysis used for hypothesis Testing is to use multiple regression analysis techniques.